A Low Input, Sustainable Production System for Fresh Market Tomatoes - Jim Rich; Fred Rhoads; Steve Olson (EDIS)
Revised! ENY-678, a 6-page illustrated fact sheet by Jim Rich, Fred Rhoads and Steve Olson, describes a system using disease resistant plant cultivars and sod-based rotation systems to replace or augment chemical alternatives to methyl bromide. Includes references. Published by the UF Department of Entomology and Nematology, May 2008.